2012
DOI: 10.1155/2012/858329
|View full text |Cite
|
Sign up to set email alerts
|

Laminar Mixing in Stirred Tank Agitated by an Impeller Inclined

Abstract: The mixing performance in a vessel agitated by an impeller that inclined itself, which is considered one of the typical ways to promote mixing performance by the spatial chaotic mixing, has been investigated experimentally and numerically. The mixing time was measured by the decolorization method and it was found that the inclined impeller could reduce mixing time compared to that obtained by the vertically located impeller in laminar flow region. The effect of eccentric position of inclined impeller on mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…In order to enhance mixing under laminar condition, many works have been reported about the advantage of utilizing unsteady impeller motion. Yao et al adopted two unsteady stirring approaches, coreverse periodic rotation and time-periodic variation of rotational speed, to enhance global mixing in a stirred tank with highly viscous fluid. Nomura et al also revealed that coreverse rotation of the impeller prevented the formation of a segregated mixing region and reduced mixing time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to enhance mixing under laminar condition, many works have been reported about the advantage of utilizing unsteady impeller motion. Yao et al adopted two unsteady stirring approaches, coreverse periodic rotation and time-periodic variation of rotational speed, to enhance global mixing in a stirred tank with highly viscous fluid. Nomura et al also revealed that coreverse rotation of the impeller prevented the formation of a segregated mixing region and reduced mixing time.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial disturbance places less demanding requirements on the machinery, so it has been widely applied in industry. Takahashi et al found that the effectiveness of setting the impeller inclined is verified through the comparison of mixing time obtained over a vertical setting impeller. Hidalgomillán et al obtained little effect of eccentricity when they investigated geometrical perturbations by using two coaxial impellers under off-centered conditions in the laminar regime, but obtained the best results with a novel configuration consisting of a dual turbine with connecting plates.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research reports have been published on the mixing times of stirred tanks with other types of impellers. The mixing time in a stirred tank can be measured experimentally using the electron conductivity method (Bujalski et al, 2002a;Giona et al, 2002), decolorization method (Aizawa et al, 2009;Takahashi et al, 2012), electrical resistance tomography (Rodgers et al, 2009(Rodgers et al, , 2011, planar laser induced fluorescence (PLIF) (Zadghaffari et al, 2009;Hu et al, 2012), and thermographic technique (Lee and Yianneskis, 1997). Ascanio (2015) summarized the methods, theories, and advantages and disadvantages of these experimental measurement techniques in detail.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of computer science, Computational Fluid Dynamics (CFD) has been widely employed to help in predicting flow distribution and mixing performance, which greatly promotes advances of the mixing studies [12,13] . Takahashi et al [14] conducted CFD simulation to study impacts of mixing paddles with different slopes on SRs and mixing time, without the investigation the blade's geometry. Qiao et al [15] studied effects of geometrical design and physical property on mixing quality of floating solids in the up-pumping PBT stirred tanks by using CFD technique qualitatively, didn't conduct the blade's optimal design.…”
Section: Introductionmentioning
confidence: 99%